Training approaches for the dissemination of clinical guidelines for NSSI: a quasi-experimental trial - König, Elisa; Hoffmann, Ulrike; Fegert, Jörg M.; Keller, Ferdinand; Sicorello, Maurizio; Spohrs, Jennifer; Kraus, Laura; Nickel, Sandra; Schmahl, Christian; Abler, Birgit; In-Albon, Tina; Koenig, Julian; et al. (Child and adolescent psychiatry and mental health, 2024)
Non-suicidal self-injury (NSSI) is of high clinical relevance due to its high prevalence and negative long-term implications. In 2016, the German consensus-based clinical guidelines for diagnostic, assessment and treatment of NSSI in childhood and adolescence were published. However, research indicates that clinical guidelines are often poorly implemented in clinical practice. One crucial part of this process is the training of healthcare professionals to transfer knowledge and capacities to bring guideline recommendations into clinical practice. The effect of three different dissemination strategies (printed educational material, e-learning, and blended-learning) on the NSSI guidelines´ recommendations was examined among 671 physicians and psychotherapists via an online-survey. The quasi-experimental study included three measurement points (before the training, after the training, 3-month follow-up) and mixed effects models were used to test for changes in knowledge, competences and attitudes toward NSSI and treatment. Moreover, the transfer of gained competences to practical work and user satisfaction were reviewed. With all three training formats, the intended changes of the outcome variables could be observed. Hereby, the printed educational material condition showed the lowest improvement in the scores for the ‘negative attitudes toward NSSI and those who self-injure’. The training effect remained stable throughout the follow-up measurement. The highest application rate of acquired intervention techniques in clinical practice was reported for the blended-learning condition. For all three training strategies, user satisfaction was high and evaluation of training quality was positive, with printed educational material receiving the lowest and blended-learning the highest evaluations. In summary, all three training formats were perceived to be of high quality and seem to be suited to cover the needs of a heterogeneous group of physicians and psychotherapists. The choice of training method could be driven by considering which training goals are desired to be achieved and by the benefit-cost ratio allowing for tailored training approaches.